Gender inclusivity in artisanal and small-scale tanzanite mining in Mererani Demarcated Area, Tanzania: A future perspective - Michael Msabi (Journal of the Geological Survey of Brazil)
This study examines the impact of Tanzania’s 2017 regulatory and institutional reforms on artisanal and small-scale mining (ASM) operations, with a focus on women’s participation in the tanzanite production value chain. Using a longitudinal research design and descriptive analysis of secondary data from the resident mine office, the study highlights significant growth in ASM activities in the Mererani area. In 2023, the ASM operators and other actors in the study area totalled 45,385 people, with men comprising 35,095 (77.33%) and women comprising 10,290 (22.67%). This indicates a substantial increase from the 4,210 people (3,231 (76.7%) men, and 979 (23.3%) women) recorded in 2018. Notably, the number of women holding mining licenses grew from 10 to 100, while female mine workers increased from 100 to 600 during the same period. Despite these advancements, men continue to dominate license-holding, although the gender gap has narrowed, indicating progress toward gender inclusion. The study also reveals a gradual expansion in tanzanite trading, with a rising number of license holders between 2018 and 2023. To further enhance women’s involvement, the paper advocates for a multifaceted approach, including targeted financial and technical support, establishment of cooperative unions, capacity building in value addition, and the creation of a more conducive operational environment. These measures are crucial for promoting equitable and inclusive economic growth in the Mererani area. The findings underscore the importance of sustained efforts to support ASM operations and promote gender equality in Tanzania’s tanzanite mining sub-sector, which remains a vital contributor to the national economy.